2021
DOI: 10.1038/s41598-021-85794-2
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends of population attributable risk of overweight and obesity for hypertension among Chinese adults from 1991 to 2011

Abstract: We determined if the increasing trend in hypertension can be partly attributed to increasing prevalence of overweight/obesity in China over the past two decades. Data were collected from 1991 to 2011 and the population attributable risk (PAR), which is used to estimate the intervention effect on hypertension if overweight/obese, were eliminated. Linear regression was used to evaluate the secular trends. The age-standardized prevalence of overweight and obesity increased by 26.32% with an overall slope of 1.27%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…By quantifying the substantial and rising absolute burden of obesity on hypertension among distinct sex-race/ethnicity subgroups using the PAF, it might also be useful concerning other countries with similar rising obesity burdens. Similarly, another study also found that the PAF of hypertension due to overweight or obesity increased from 27.1 % in 1991 to 44.6 % in 2011 in China ( Gou and Wu, 2021 ). Given the morbidity and mortality associated with hypertension ( Aune et al, 2021 ), it is important to control obesity to reduce the prevalence of hypertension, thereby reducing the burden of hypertension-induced CVD.…”
Section: Discussionmentioning
confidence: 88%
“…By quantifying the substantial and rising absolute burden of obesity on hypertension among distinct sex-race/ethnicity subgroups using the PAF, it might also be useful concerning other countries with similar rising obesity burdens. Similarly, another study also found that the PAF of hypertension due to overweight or obesity increased from 27.1 % in 1991 to 44.6 % in 2011 in China ( Gou and Wu, 2021 ). Given the morbidity and mortality associated with hypertension ( Aune et al, 2021 ), it is important to control obesity to reduce the prevalence of hypertension, thereby reducing the burden of hypertension-induced CVD.…”
Section: Discussionmentioning
confidence: 88%
“…24 In addition, the lifestyle modifiable risk factors have been proved to contribute substantially to chronic disease. [25][26][27] Paired with the high prevalence of common chronic diseases, the need for health promotion and intervention among PHPs is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the incidence of hypertension has increased in China, partially due to an increase in the prevalence of overweight/obese (OW/OB) individuals [ Gou and Wu, 2021 ]. Although not all obese patients will eventually develop hypertension [ Natsis et al, 2020 ], it is relatively difficult to treat obese patients with hypertension due to drug resistance [ Rosolová, 2020 ].…”
Section: Introductionmentioning
confidence: 99%